Magnetization Process and Interlayer Coupling in MnNi/Co/Ag(Cu)/Py High-Temperature Annealed Spin Valves - Tuan, N. A.; Su, L. V.; Dung, T. T. Hoai; Tue, N. A.; Khanh, H. Q. (Old Journal, 2019)
MnNi/Co/Ag/Py and MnNi/Co/Cu/Py spin valves, where Py is the symbol for permalloy Ni81Fe19, were prepared using magnetron sputtering followed by a high temperature annealing at Ta=300°C and 400°C for 30 minutes in high vacuum ( 10-5 torr). The magnetization process and the magnetic coupling between ferromagnetic layers of these spin valves were investigated. The results show a weak magnetic coupling behavior, moreover, a weak positive exchange bias coupling between Co and Py layers, and a trend of an out-of-plane magnetic anisotropy in these spin valves. The origin of these features or behaviors are discussed in detailed. These results will be useful information for technological adjustments to achieve the expected properties for magnetic coupling and magnetic anisotropy of the spin valve devices.